Svalbox-DOM_2021-0056 ... - Betlem, Peter; Oldfield, Simon; Kelly, Ian; Lindell, Elise Hélene Anette; Svalbox Team (Zenodo, 2023)
Model description: The Konusdalen outcrop provides an excellent exposure of the reservoir sequences targeted by the Longyearbyen CO2 Lab.The upper part of De Geerdalen Formation is visible along with the Slottet bed and first two Sequences of the Wilhelmhøya Subgroup.The entire section is affected by through-going faults (ENE) and is heavily fractured. Data availability: All uploaded archives are to be extracted to the same directory for a functional working environment, i.e., at the very least consisting of a project folder with the data and metashape subdirectories. The included processing report specifies the processing parameters that were used as input for the processing software (Agisoft Metashape, v2.0.1.15925). Georeferencing data use CRS epsg:32633.Exported model data use CRS epsg:32633. Show and visualise on Svalbox.no: Through Svalbox we aim to take geoscientific research and education to the next level – with the simple motto of placing all key information and data sets in their correct spatial ...